Arylsulfamates inhibit colonic Bacteroidota growth through a sulfatase-independent mechanism - Conor J. Crawford; Charles W. E. Tomlinson; Christian Gunawan; Zongjia Chen; Dominic P. Byrne; Cosette Darby; Martina L. G. Conti; Tony Larson; Ana S. Luis; Stefano Elli; Edwin A. Yates; David N. Bolam; et al. (Proceedings of the National Academy of Sciences, 2025)
Excessive degradation of the colonic mucin layer by Bacteroides within the human gut microbiota drives inflammatory bowel disease (IBD) in mice. Bacterial carbohydrate sulfatases are key enzymes in gut colonization, and they are elevated in human IBD and correlate with disease severity. Selective inhibitors of carbohydrate sulfatases could function as sulfatase-selective drugs, allowing precise control of sulfatase activity while preserving these otherwise beneficial bacteria. Arylsulfamates are covalent inhibitors that target a catalytic formylglycine residue of steroid sulfatases, a residue that is also conserved in carbohydrate sulfatases. Here, we find that a library of aryl- and carbohydrate sulfamates is ineffective against carbohydrate sulfatases, yet can inhibit human gut microbiota (HGM) species grown on sulfated glycans. Leveraging thermal proteome profiling (TPP), we identify a lipid kinase as the target responsible for these effects. This work highlights the imperative for developing specific inhibitors targeting carbohydrate sulfatases and reveals the adverse effects that arylsulfamates have on Bacteroides species of the HGM.